(untitled) (Web of Teachers: Inderscience Research, 2024)
This study investigates the optimization of online learning models to enhance student engagement and improve learning outcomes. With the rise in digital education, understanding effective strategies for virtual environments has become crucial for educators and institutions alike. This research explores various online learning models, focusing on elements that contribute to increased engagement, such as interactivity, gamification, and real-time feedback, while assessing their impact on measurable learning outcomes. Using a mixed-method approach, including surveys, engagement tracking, and outcome assessments, we analyze which models foster the highest levels of motivation and academic achievement. Findings indicate that interactive and gamified models lead to significantly improved engagement and outcomes compared to traditional approaches. The study concludes with recommendations for implementing optimized learning models that support both student motivation and academic success, providing a framework for future development in online education.